Microfinance and Women's Empowerment in Bangladesh Unpacking the Untold Narratives - Nawaz, Faraha (Springer International Publishing : Imprint: Palgrave Pivot, 2019)
This book examines the effects of policies and practices of microfinance NGOs in empowering rural women in Bangladesh. Nawaz seeks to unpack the untold narratives of women's empowerment and to fill the current knowledge gap in this area. The book goes beyond the narrow minimalist evaluation of microfinance that only focuses on women's economic empowerment through their ability to access financial resources. Rather, it looks at whether and how microfinance empowers women in a holistic manner across the socio-cultural, psychological and political spheres of life. The author argues that microfinance reduces levels of poverty, which means that women are better able to meet their practical gender needs; however, they are not empowered unless they are also able to meet their strategic gender needs, including the transformation of gender power relations from the household to state arenas. Therefore, the book argues that in order to bring about higher levels of empowerment, microfinance programs must be combined with other services such as financial literacy, socioeconomic training, education, healthcare, social mobilization and legal support. Microfinance and Women's Empowerment in Bangladesh will be of interest to students and scholars across a range of disciplines, including Gender Studies, Development Studies, and Politics.